Liquidity Management, Capital Structure and Their Impact on Profitability: A Study of Selected Listed Beverage, Food and Tobacco Firms in Colombo Stock Exchange (CSE) in Sri Lanka - Anojan, V. (University of Jaffna, 2014)
The focus of this study is to identify significant impact of liquidity management and capital structure on profitability and find the association between capital structure, liquidity management and profitability of selected listed Beverage, Food and Tobacco firms in Colombo Stock Exchange (CSE) from the financial year 2008 to 2012. Many researchers stated that liquidity management is vital for the firms to maintain its profitability through their research findings and also liquidity management theory states there is negative association between liquidity position and profitability. Capital structure is vital in determining the return on equity (ROE). Most of Beverage, Food and Tobacco firms have not too much of current assets and current liabilities than other business firms, it can be seen through their financial statements due to that there is question whether liquidity management necessary to this type of firms. Regression and Correlation analysis were performed in this study. Regression results confirmed that there is (R2 = 0.104) no significant impact of capital structure on the profitability and also there is (R2 = 0.068) no significant impact of liquidity management on profitability. Correlation results confirmed that there is (P = 0.435) no significant association between capital structure and profitability and also there is (P = 0.531) no significant association between liquidity management and profitability. It implies that the liquidity management and capital structure has little role in Beverage, Food and Tobacco firms. Although this study supports the number of earlier studies, it could not provide the conclusive evidence on some important issues. The differences in the results from earlier studies suggest that liquidity management and capital structure design in selected firms may not be similar to that of other industries.
Keywords: Liquidity Management; Capital Structure; Profitability; Listed Firms; Beverage Food & Tobacco